Determinants of health literacy in the general population: results of the Catalan health survey - Oriol Garcia-Codina; Dolors Juvinyà-Canal; Paloma Amil-Bujan; Carmen Bertran-Noguer; María Asunción González-Mestre; Eulàlia Masachs-Fatjo; Sebastià J. Santaeugènia; Pilar Magrinyà-Rull; Esteve Saltó-Cerezuela (BMC, 2019)
Abstract Background Health Literacy (HL) is the knowledge and competence to access, understand, appraise, and apply health information for health judgment. We analyze for the first time HL level of Catalonia's population. Our objective was to assess HL of population in our area and to identify social determinants of HL in order to improve the strategies of the Healthcare Plan, aimed at establishing a person-centered system and reducing social inequalities in health. Methods This was a cross-sectional study based on the Health Survey for Catalonia (ESCA, Enquesta de Salut de Catalunya), which included the 16 items of the European Health Literacy Survey Questionnaire (HLS-EU-Q16). The statements in the questionnaire cover three different health literacy domains: Health Care, Disease Prevention, and Health Promotion. HL was categorized in three levels: Sufficient, Problematic and Inadequate. Chi-square tests were performed to compare the percentages of subjects with adequate or inadequate HL across sociodemographic and health-related variables. Variables showing significant differences were included in a stepwise logistic regression to predict inadequate HL level. Results The questionnaire was administered to 2433 subjects aged between 15 and 98 years old (mean of 45.9 years, SD 18.0). Overall, 2059 subjects (84.6%) showed sufficient HL, 250 (10.3%) inadequate HL, and 124 (5.1%) problematic HL, with no significant differences between men and women (p = 0.070). A logistic regression analysis showed that low health literacy is associated with a lower level of education (OR 2.08, CI 95% 1.32-3.28, p = 0.002), low socioeconomic status (OR 2.11, CI 95% 1.42-3.15, p <  0.001) and a physical limitation to perform everyday activities (OR 2.50, CI 95% 1.34-4.66, p = 0.004). We also found a more modest association with low physical activity, having a self-perceived chronic disorder and performing preventive activities. Conclusions Catalonia has a high percentage of subjects with sufficient HL. Education level, socioeconomic status and physical limitations were the factors with the strongest contribution to inadequate or problematic health literacy. Although these results are likely to be country-specific, the factors identified will allow policymakers of areas with similar socioeconomic profiles to identify groups with high risk of problematic or inadequate HL, which is essential for a successful patient-centered model of care.